Economic evaluation of hepatocellular carcinoma surveillance in chronic hepatitis B patients with virological remission - Fang, Kailu; Li, Shuwen; Lin, Yushi; Zhang, Yu; Wu, Jie (BMC public health, 2024)
Background Subsequent risk of hepatocellular carcinoma (HCC) persists in chronic hepatitis B (CHB) patients with virological remission. We aimed to assess the cost-effectiveness of HCC surveillance in those patients and determine appropriate age to commence or discontinue surveillance. Methods We developed an individual-based state transition model, simulating the advancement of HCC in CHB patients with virological remission. We used this model to compare the incremental cost-effectiveness ratio (ICER) and long-term health outcomes of biannual or annual HCC surveillance for varying durations with no surveillance. Results For compensated cirrhosis patients with CHB, biannual surveillance was not cost-effective for all age groups, while annual surveillance was cost-effective for patients aged 55 to 70 (ICER USD 28,076 / quality-adjusted life years [QALY] gained), which detected 176 additional early HCC cases in a 100,000-person cohort compared to no surveillance. In CHB patients with advanced fibrosis, annual surveillance for patients aged 40 to 75 was the most cost-effective strategy (ICER USD 4,984/QALY gained), which detected 289 additional early HCC per 100,000 patients. Conclusions Annual surveillance for patients with compensated cirrhosis or advanced fibrosis was a more cost-effective option that demonstrated substantial economic benefits, being slightly less effective than biannual surveillance at a significantly lower cost, providing insights for professionals in evaluating HCC surveillance among high-risk patients in China. Lay summary The most cost-effective age group for surveillance of hepatocellular carcinoma (HCC) varied depending on the stage of the disease. Regular annual surveillance for patients with compensated cirrhosis or advanced fibrosis was more cost-effective option, showing great economic and clinical benefits with slightly less effective than biannual surveillance but significantly lower cost.